Prospects for New Physics in Kaon Decays - Polonsky Zachary (EPJ Web of Conferences)
In these proceedings, we give an overview of the current status and future prospects of new physics searches using rare kaon decays. We discuss several promising observables whose experimental or theoretical precisions can be reasonably–and in several cases substantially–reduced in the near future. We emphasize the complimentarity of charged and neutral kaon programs in their ability to both probe a wide array of new physics scenarios and test qualitatively different physics.